Reinterpretasi Konsep Nushuz: Falsifikasi Konsep Kebolehan Suami Memukul Istri - Ach Fajruddin Fatwa (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2005)
This study aims to reexamine the concept of nushuz in Islam and criticize the view that allows husbands to beat their wives as a form of discipline. This study uses a qualitative method with a hermeneutic approach and discourse analysis of verses from the Qur'an, hadiths, and classical and contemporary tafsir. The results showed that the concept of nushuz does not always mean wife's defiance, but reflects the dynamics of husband-wife relations which must be resolved with the principles of justice and compassion. The interpretation that allows beatings is more influenced by patriarchal culture than by universal Islamic values. This reinterpretative approach emphasizes that Islam encourages the resolution of domestic conflicts through deliberation and a non-violent approach. Thus, the concept of nushuz needs to be understood in the context of gender justice that is more humanistic and in accordance with the values of maqashid sharia.